Jaminan Sosial Berbasis Komunitas: Respon Atas Kegagalan Negara dalam Penyediaan Jaminan Kesejahteraan - Suparjan, - (Jurnal Ilmu Sosial dan Ilmu Politik, 2010)
Various findings in the research showed that government failed to provide social security as one of strategies to overcome problem of social welfare, especially to people who live under the poverty line. This research showed that there are problems contributing to the government failure in maintaining community welfare through social security. Moreover, due to fulfill of social welfare, this research showed that Lembaga amil zakat infaq sodaqoh Tsalatsatun Kharimah appears as a way to distribute zakat from the have community to the poor in its region since 2006. Institutionalizing process of the zakat distribution may through efforts of building collective awareness by showing positive work for community.